10.1002/9781118797914 (CrossRef Listing of Deleted DOIs, 2000)
Ovarian leiomyomas, either primary or parasitic in origin, are exceptionally rare and account for about 0.5% to 1% of all benign ovarian tumors. They often pose a diagnostic challenge, particularly in postmenopausal women, as they can clinically and radiologically mimic ovarian malignancy. Histopathological confirmation remains essential, and complete surgical excision yields an excellent prognosis. To our knowledge, the present report represents one of the few reported cases of primary ovarian leiomyoma in a postmenopausal woman from Sub-Saharan Africa. We report a case of primary ovarian leiomyoma in a 78-year-old postmenopausal woman (P2L2) who presented to a tertiary referral center in Northern Tanzania with a 1-year history of gradual onset abdominal pain and distension. She had a 20-year smoking history and long-term use of combined oral contraceptive pills. Laboratory findings showed mild anemia (hemoglobin 9.2 g/dL) with normal serum CA-125 (20 U/mL) and carcinoembryonic antigen (3 ng/mL). Physical examination revealed abdominal distension, tenderness in the right lower quadrant, and a palpable pelvic mass with full vaginal fornices. Contrast-enhanced computed tomography demonstrated a large 15 × 11 × 16 cm multiloculated cystic mass with internal septations arising from the right adnexa, extending to the subhepatic region, causing significant mass effect on adjacent structures including the right kidney and bowel loops. Multiple uterine fibroids were also noted. She underwent a total abdominal hysterectomy (TAH) with bilateral salpingo-oophorectomy (BSO). Histopathological examination revealed a well-circumscribed tumor comprised of smooth muscle with degenerative change, bundles of interlacing fascicles without atypia. Immunohistochemical analysis demonstrated strong positivity for smooth muscle actin (SMA) and desmin in the tumor cells. Overall, the findings are consistent with a diagnosis of ovarian leiomyoma with degenerative changes. The postoperative period was uneventful, and the patient was discharged three days postoperatively. At regular follow-up, there has been no evidence of recurrence.